1958
DOI: 10.3181/00379727-98-24025
|View full text |Cite
|
Sign up to set email alerts
|

Growth-Promoting Properties of Pyruvate, Oxalacetate, and  -Ketoglutarate For Isolated Walker Carcinosarcoma 256 Cells

Abstract: 0 50 100 150 200 0 50 100 150 ZM) 0 50 100 150 200 T I M E I N M I N U T E S TUMOR DNA CELLS * NORMAL DNA CELLS UNCOUPLED CELLS I'lG. 2. Effect of DNA-ase upon settling rate of coupled and uncoupled cells in presence of rabbit antiserums and normal rabbit serum.substance to stimulate antibody formation or to be detected by precipitin or agglutination reaction. However, it must be admitted that it is difficult at present to understand why a hapten of the complexity of DNA would not precipitate with antiserum. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1959
1959
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Among them, the biological effects of Krebs cycle metabolites, such as succinate, have been scarcely evaluated. Some have been reported to show angiogenic properties in vitro [73][74][75]. It has recently been demonstrated that succinate specifically binds and signals through the G protein-coupled receptor GPR91 [76], but its physiological role remained poorly characterized.…”
Section: Succinate Receptor Gpr91mentioning
confidence: 99%
“…Among them, the biological effects of Krebs cycle metabolites, such as succinate, have been scarcely evaluated. Some have been reported to show angiogenic properties in vitro [73][74][75]. It has recently been demonstrated that succinate specifically binds and signals through the G protein-coupled receptor GPR91 [76], but its physiological role remained poorly characterized.…”
Section: Succinate Receptor Gpr91mentioning
confidence: 99%
“…Each tube received 2 ml of a medium consisting of Hanks' balanced salt solution to which were added glucose (up to 22 m~), in~sitol (2 rag/ liter), and mixtures of vitamins (25), antibiotics, and amino acids (26) from which either isoleucine or lysine had been omitted. Uniformly labeled C14-L-lysine (605 (/zc/mg) and C14-Lisoleucine (675 #c/rag), obtained from the Institut Pasteur, Paris, were added to a concentration of 2/zc/ml.…”
Section: Materials and Methods Preparation Of Tissuementioning
confidence: 99%
“…The culture medium [28] consisted of HBSS plus 0.5% dextrose, 0.5% ovalbumin, 1% BME-vitamins (100 X concentrate), penicillin G (100 U/ml), and an amino acid mixture [13] from which L-lysine and L-isoleucine were omitted. The pH was adjusted to 7.4 with sodium bicarbonate.…”
Section: Culture Mediummentioning
confidence: 99%